2020
DOI: 10.3390/cryst10110995
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cavity Structure on Acoustic Characteristics of Phononic Crystals Based on Double-Layer Plates

Abstract: Localized resonance phononic crystals (LRPCs) are increasingly attracting scientists’ attention in the field of low-frequency noise reduction because of the excellent subwavelength band gap characteristics in the low-frequency band. However, the LRPCs have always had the disadvantage that the noise reduction band is too narrow. In this paper, in order to solve this problem, LRPCs based on double-layer plates with cavity structures are designed. First, the energy bands of phononic crystals plate with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…They found that such a system can easily activate the coupling effects between the resonators to obtain a broadband gap of 590 to 3220 Hz. Chen et al [18] studied the acoustic performance of doublelayer plates cavity. It was observed that within a certain limit a better noise attenuation performance can be attained when the volume of the cavity was increased.…”
Section: Introductionmentioning
confidence: 99%
“…They found that such a system can easily activate the coupling effects between the resonators to obtain a broadband gap of 590 to 3220 Hz. Chen et al [18] studied the acoustic performance of doublelayer plates cavity. It was observed that within a certain limit a better noise attenuation performance can be attained when the volume of the cavity was increased.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of industry, double-layer structures with the multifunctional characteristics, such as light weight, large stiffnes, good impact resistance and so on, have been widely used in the field of naval architecture, aeronautics, astronautics, civil engineering and so on [4] . Moreover, the cavity of a double-layer structure in engineering is generally periodically added sandwich to enhance structural performance, which makes the double-layer structures have an excellent convergence point with PCs [5] . Hence, based on the common application background in acoustical devices of NEMS and PCs, excellent characteristics of piezoelectric nanostructures, PCs and double-layer structures will be gathered, and the new coupling physical characteristics will be displayed if the…”
mentioning
confidence: 99%